Applying Discourse Network Analysis in Journalism Studies: Exploring Digital Transformation Response - Bakry, Gema Nusantara; Ardianto, Fetra (Universitas Muhammadiyah Yogyakarta, 2025)
The digital transformation has reshaped the media industry, moving from traditional models to technology-driven approaches such as content personalization and direct-to-consumer (D2C) streaming. In journalism research, Discourse Network Analysis (DNA) has emerged as a novel method to map relationships among actors, discourses, and narratives across platforms. By integrating quantitative and qualitative approaches, DNA offers comprehensive insights into media discourse dynamics. In Indonesia, its application remains limited, addressing issues like gig economy policies, sexual violence, and peatland restoration. Supported by frameworks such as the Advocacy Coalition Framework and Collaborative Governance Theory, DNA enables the analysis of conflicts of interest, coalitions, and ideological shifts. However, Indonesian research often emphasizes quantitative approaches, overlooking qualitative insights essential for contextualizing discourse. Unlike linear-focused methods such as content or critical discourse analysis, DNA excels in the significant data era by processing large-scale social media content, integrating textual and relational data, and visualizing complex communication networks. This makes it particularly valuable for understanding how information flows and evolves, offering strategic insights into shifting communication patterns, media consumption behaviors, and audience engagement in the digital age.